1951
DOI: 10.1037/h0053745
|View full text |Cite
|
Sign up to set email alerts
|

Variability of reaction time and susceptibility to automobile accidents.

Abstract: Reactions to visual and auditory stimuli are made more or less continuously by the automobile driver, particularly on a heavily-traveled street or highway. Individual differences exist in the speed with which drivers are able to respond to these stimuli. Measurements of reaction time have been traditionally included in experimental test batteries designed to predict accident susceptibility of drivers, on the premise that the number of accidents or the accident-rate of an individual driver is partially a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1961
1961
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The predictor in this study had a logical relationship to the criterion behavior. Often simple brake reaction to a red light is correlated with accident records (e.g., Cation, Mount, & Brenner, 1951) where there is little correspondence between the braking response elicited by the red light and the complex perceptual process in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…The predictor in this study had a logical relationship to the criterion behavior. Often simple brake reaction to a red light is correlated with accident records (e.g., Cation, Mount, & Brenner, 1951) where there is little correspondence between the braking response elicited by the red light and the complex perceptual process in the real world.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the criterion, culpability should mean that the drivers were to some extent a cause of the event due to their driving behaviour. However, criterions for this would seem to differ between studies, because, although the criterion itself is almost never reported, the differing percentages of culpable drivers between studies (compare for example Cation, Mount & Brenner, 1951;Brandaleone & Flamm, 1955;Quimby, Maycock, Carter, Dixon & Wall, 1986;Dobson, Brown, Ball, Powers & McFadden, 1999), as well as the correlations between culpable and non-culpable in different studies (e.g. Goldstein & Mosel, 1958;McBain, 1970;Gully, Whitney & Vanosdall, 1995;Arthur & Graziano, 1996), show that in many cases, the criterion does not achieve what it set out to do with any large degree of precision (af Wåhlberg & Dorn, 2007).…”
Section: Figure 1 About Herementioning
confidence: 99%
“…Although some effects of age and/or experience can almost always be found in crash risk calculations, there exists an inherent problem in such data; the matter of culpability for crashes, which is often not taken into consideration. As all drivers are exposed to events that are due to other drivers' behavior, studies that use all crashes as the dependent measure, instead of culpable ones, probably underestimate the effects of their independent variables (studies that have found this effect include References 26–29).…”
Section: Introductionmentioning
confidence: 99%